On the Nexus Between Currency Risk and Hedging Across Different Time Scales: Evidence From Healthcare Firms in Malaysia - Hishamuddin Abdul Wahab (Global Academy of Training and Research (GATR) Enterprise., 2026)
Indexed by MyCite